Fractie van 1905 tot 1909; bij het afscheid van van Kol. V.l.n.r.: Helsdingen, Troelstra, Schaper, Ter Laan, Hugenholtz, Van Kol (1909)
Fractie van 1905 tot 1909; bij het afscheid van van Kol. V.l.n.r.: Helsdingen, Troelstra, Schaper, Ter Laan, Hugenholtz, Van Kol.